2020
DOI: 10.1088/1361-648x/ab6428
|View full text |Cite
|
Sign up to set email alerts
|

Role of W-site substitution on mechanical and electronic properties of cubic tungsten carbide

Abstract: In order to understand the role of W-site substitution on properties of cubic tungsten carbide (β-WC), we have investigated the structural, mechanical, and electronic properties of WXC 2 (X = Si,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 101 publications
(137 reference statements)
0
3
0
Order By: Relevance
“…The authors would also like to mention that, WC usually has a hexagonal (HCP) structure but may have an FCC structure at high temperatures as mentioned earlier. 31,32,35,36 As a matter of fact, we also calculated cohesive energies and formation energies of the metal-substituted tungsten carbides in FCC structure, in comparison with those of the carbides in the HCP structure. Table 2 provides the calculated energies of a few representative carbides for quick comparison.…”
Section: Stability Analysis Based On Cohesive and Formation Energiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors would also like to mention that, WC usually has a hexagonal (HCP) structure but may have an FCC structure at high temperatures as mentioned earlier. 31,32,35,36 As a matter of fact, we also calculated cohesive energies and formation energies of the metal-substituted tungsten carbides in FCC structure, in comparison with those of the carbides in the HCP structure. Table 2 provides the calculated energies of a few representative carbides for quick comparison.…”
Section: Stability Analysis Based On Cohesive and Formation Energiesmentioning
confidence: 99%
“…By strengthening the softest elastic mode of tungsten carbide, the authors demonstrated that WC can be hardened by alloying with N or Re via Fermi‐level tuning. More recently, Augustine et al 31 studied the role of W‐site substitution on mechanical and electronic properties of cubic WC with first‐principles calculations (the cubic WC is stable only at high temperatures >2525°C 32 ). Some new stable compounds (CrWC 2 , NbWC 2 , ScWC 2 , YWC 2 , and UWC 2 ) with reasonably good hardness were predicted.…”
Section: Introductionmentioning
confidence: 99%
“…The strong and on-site coulombic interactions can be well described by introducing the Hubbard U parameters, and it is easy to figure out the band gap value close to the experimental value. In this paper, the U value of oxygen 2p, titanium 3d, niobium 4d, tantalum 5d, tungsten 5d and molybdenum 4d orbital electrons were set as 5.25 eV, 2.8 eV, 4 eV, 4.5 eV, 4 eV, and 4.38 eV, respectively [37][38][39][40][41]. First, all model structures were fully optimized to their respective energy minimum before doing further photoelectric properties calculations.…”
Section: Calculation Models and Methodsmentioning
confidence: 99%